An Analysis Protocol for Three-Electrode Li-Ion Battery Impedance Spectra: Part II. Analysis of a Graphite Anode Cycled vs. LNMO. Issue 10 (11th July 2018) - Pritzl, Daniel; Landesfeind, Johannes; Solchenbach, Sophie; Gasteiger, Hubert A.
Abstract : Lithium-Ion batteries consisting of LNMO (LiNi0.5 Mn1.5 O4 ) cathodes and graphite anodes show severe capacity fading at elevated temperatures due to a damage of the solid electrolyte interface (SEI) on the anode. Hence, a detailed investigation of the anode with electrochemical impedance spectroscopy (EIS) can provide valuable insight into the phenomenon of anode degradation. In this study, we use a modified version of our novel impedance procedure (Part I of this study), where the anode impedance is measured at non-blocking conditions (10% SOC) and blocking conditions (0% SOC) in a graphite/LNMO full-cell with a gold wire micro-reference electrode (GWRE). We show that during cycling an ionic contact resistance ( R Cont.Ion ) at the separator/anode interface evolves, which is most likely caused by manganese dissolution from the high-voltage cathode (LNMO). By simultaneously fitting EIS spectra in blocking and non-blocking conditions, we can deconvolute the anode impedance evolving over 86 cycles at 40°C into contributions of: a) the separator resistance ( R Sep. ), b) the true charge transfer resistance ( R CT ), and, c) the ionic contact resistance ( R Cont.Ion ) evolving at the separator/anode electrode interface. We also show that the main contributor to a rising anode impedance is the ionic contact resistance ( R Cont.Ion ).